Fiscal Policy and Stock Markets during the Financial Crisis - Łon , Eryk (Studia Oeconomica Posnaniensia, 2014)
This article investigates links between the nature of fiscal policy and the situation on stock markets. The study was conducted on the markets of developed and emerging economies. An expansionary fiscal policy in a given year usually leads to a bull market in the following year, whereas a restrictive fiscal policy leads to a bear market. During the financial crisis, implementing a restrictive fiscal policy resulted in a stock market downturn. In 2009 introducing an expansionary fiscal policy in the U.S improved the situation on developed and emerging markets.